Antimicrobial resistance and genetic diversity of Campylobacter spp. isolated from broiler chicken at three levels of the poultry production chain in Costa Rica - Lazo Láscarez, Sabrina (2021)
This research was supported by the Universidad Nacional, Costa Rica, as part of FIDA project 054541-0000, entitled “Prevalencia, caracterización molecular y perfil de resistencia a antibióticos de Campylobacter spp. en pollo para consumo humano de Costa Rica.” The contributions from the personnel at the Bacteriology Laboratory, Escuela de Medicina Veterinaria, Universidad Nacional, and the National Reference Centre for Microbiological Food Safety of Costa Rican Institute for Research and Education in Nutrition and Health during the sample processing are highly appreciated.